2014
DOI: 10.3126/jnps.v34i1.9056
|View full text |Cite
|
Sign up to set email alerts
|

Acute Lymphoblastic Leukemia: Fourteen Years Experience of a Single Institution

Abstract: Introduction: Leukemia commonly known as blood cancer is the most common malignant neoplasm in childhood accounting for about 41 % of all malignancies that occur in children younger than 15 year of age. The objectives of this study were to find out the clinico-laboratory features and survival of children with acute lymphoblastic leukemia (ALL) during fourteen years in pediatric oncology unit of a tertiary care hospital. Materials and Methods: This was a retrospective study conducted at Kanti Children's Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…A study from Pakistan also showed similar results, where fever (80.4%), pallor (46.4%), and weakness (46.4%) were the most common clinical features in AML patients 10 . However, in one study conducted in Kanti Children Hospital, Nepal, the most common presenting features in ALL, closely related to AML, were fever (89.2%), followed by splenomegaly (89.1%), hepatomegaly (69.2%), and lymphadenopathy (58.4%) 12 .…”
Section: Discussionmentioning
confidence: 99%
“…A study from Pakistan also showed similar results, where fever (80.4%), pallor (46.4%), and weakness (46.4%) were the most common clinical features in AML patients 10 . However, in one study conducted in Kanti Children Hospital, Nepal, the most common presenting features in ALL, closely related to AML, were fever (89.2%), followed by splenomegaly (89.1%), hepatomegaly (69.2%), and lymphadenopathy (58.4%) 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar L2-ALL predominance was observed by Nasim et al however Humayun et al and Gupta showed L1 as the most common subtype. [37][38][39] Usually ALL subtype is more prevalent in children younger than 15 40 As all of our respondents were aged more than 13 years old, real scenario may come out altered here. Total patients su ering from AML were.…”
Section: Discussionmentioning
confidence: 99%
“…2 , 3 Data published from Nepal on 300 patients of childhood ALL between 1998 and 2012 showed a 5-year EFS of 28% only. 4 Data on survival outcome are even more limited in the adult population, and there is no evidence originating from LMICs to concur with the survival data from the developed countries. The health care system in Nepal only has a handful of medical centers in large cities which provide oncology services to the entire population.…”
Section: Introductionmentioning
confidence: 99%